PEMBUATAN GAME MOBILE BAYMAX RUN - Garry Wiratama; Tony Tony; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Baymax Run is a mobile running game.  Players must run to get the highest score in the game. Six different character with the ability each ready to help players to reach the highest score. Baymax Run created by game engine Unity and C# as programming language. Baymax Run made for mobile smartphone and can only be run on Android smartphone. Key wordsBaymax Run, Running Game, Unity, C#, Mobile Game